Ning Umi Laila's Nasyid Da'wah Strategy That Inspires Millennials - Didik Himmawan; Rodotul Janah (Konsultan Jurnal Ilmiah Indonesia, 2024)
This paper aims to examine the Da'wah of Ning Umi Laila's Awesome Nasyid. Da'wah is an obligation for Muslims and Muslim women at all times and conditions. In her da'wah, Ning Umi Laila uses Nasyid as a way to convey religious knowledge to da'wah partners. songs that contain word art with Islamic nuances. Through the lyrics of the song nasyid can be used as a memorable da'wah message, Ning Umi Laila Rahmah Hadi preaches by slipping sholawat / nasyid with the aim that the congregation does not feel bored and entertained, so that with this da'wah method Ning Umi Laila is loved by the Millennials and Z.